ATTITUDES AND AWARENESS OF HIGH SCHOOL STUDENTS ABOUT HEALTHY EATING AND BEHAVIOR - Albena Andonova; Deyana Todorova; Monika Obreykova (Peytchinski Publishing, 2022)
Social networks, television, and mass media are spread diverse and attractively presented information about food, diets, and culinary shows, which in most cases give not entirely reliable information about diets and products. Purpose: The Purpose of the study is to establish the attitude and awareness of high school students about healthy eating and behavior. Methods: The anonymous survey involved 111 students (59 girls and 52 boys) aged 15 to 19 randomly selected. Results: The survey found that half of the students are familiar with the basic principles of healthy diet, have followed a diet at least once, prefer to be informed about healthy diet by people who have changed their diet and have achieved optimal health and vision. A little over half of the respondents want to change their diet in order to lose weight, 31.5% are willing to participate in training on healthy diet, and 40.5% are hesitant. Preferred healthy eating tipsters are athletes (38.7%), medical professionals (36.9%), celebrities (36%), influencers (34.2%) and vloggers (32.4%). Conclusions: the study found that about half of the surveyed students show an active interest in healthy eating, their main motive is to change their diet in order to improve their appearance and on this occasion, they followed a diet. Conducting active information campaigns to promote healthy eating on the Internet and social networks with the help of people who have achieved good physical shape and optimal level of health will attract more young people to a healthy lifestyle.